HUBUNGAN ANTARA KECERDASAN EMOSIONAL DENGAN STRES KERJA PERAWAT PADA PT NUSA LIMA MEDIKA PEKANBARU - Gultom, Elida (Sekolah Tinggi Ilmu Ekonomi Riau, 2022)
Nurses in charge of serving patients are very susceptible to work stress due to their low emotional intelligence. This study aims to determine whether there is a relationship between emotional intelligence and work stress of nurses at PT Nusa Lima Medika Pekanbaru. The measuring instrument used in this research is the emotional intelligence scale and the work stress scale. The population in this study were nurses at PT. Nusa Lima Medika Pekanbaru, totaling 56 people. The sample technique used is a saturated sample so that a total sample of 56 respondents is obtained where the data collection technique is through a questionnaire conducted online. The data analysis technique used is product moment correlation using SPSS 23.0 for windows. Based on the results of descriptive data analysis, the emotional intelligence of nurses at PT. Nusa Lima Medika is in the moderate level and the work stress of nurses is also in the moderate category. The results of hypothesis testing found that there was a negative correlation between emotional intelligence and work stress of nurses at PT. Nusa Lima Medika Pekanbaru with an r value of -0.487. The higher the emotional intelligence of nurses, the lower the work stress of nurses and vice versa.